Effects of Trauma and Postmigration Stress on Refugee Women's Health: A Life Course Perspective - Sangalang, Cindy C; Vang, Cindy; Kim, Bum Jung; Harachi, Tracy W (Social work (New York), 2022)
Trauma exposure and postmigration stress are associated with adverse health outcomes among refugees, yet the relative effect of these factors for subgroups of refugees and those resettled long-term remains unclear. Drawing on life course theory, this study evaluated the associations between war trauma, postmigration stress, and health among Southeast Asian refugee women in the United States, and whether these patterns differ across the life span. A community sample of Vietnamese and Cambodian refugee women aged 30-72 years (N = 293) reported mental and physical health outcomes, conflict-based trauma exposure, and postmigration measures of discrimination and community violence. Both trauma exposure and discrimination were associated with mental and physical health problems, with the relative effect of each stressor varying across specific health outcomes; community violence was associated with poorer mental health. Age moderated the effect of trauma exposure across health outcomes, with stronger associations between trauma and health for older women in particular. Findings provide support for the influence of trauma exposure and the importance of postmigration stressors on health across the life span for refugees. Attending to age group differences in the effects of these stressors, and to subgroups such as women, has implications for interventions addressing the long-term health of refugee populations.